Peculiarities of adaptation of high-performance Lithuanian swimmers to physical loads over a four year Olympic cycle - Dadeliene, R.; Skernevicius, J.; Pavlovskaja, L. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2002)
The aim of the current study was to study and summarize the bodily adaptation peculiarities of the Lithuanian national Olympic team swimmers over a four-year Olympic cycle. Results. In the four year of the Olympic cycle, single muscular contraction power on average increased from 2104.83 W to 2420.37 W and the relative index per 1 kg of body mass increased by 4.42 W/kg. Anaerobic alactic muscular power showed a less dramatic increase. For swimmers in whom these indices were high at the beginning of the Olympic cycle the change was insignificant, while for those who showed the low indices at the beginning of the cycle their increase was considerable. The individual indices of special performance over the for-year Olympic cycle showed a very significant progress. In the last year of the cycle the 60-s work power on a swimming ergometer increased on average by 26W, the dispersion range being from 240 W to 316 W. The percentage of dispersion (9.36%) was not high. However, both in the earlier studies and in the last examination before the Olympic Games we observed a significant decrease of power throughout the whole 1-minute test. Though this feature over the four years showed a decreasing tendency, we failed to attain its good stability. The functional capacity of the circulatory and respiratory systems showed a pronounced improvement in young swimmers, whereas in adults its annual variations were insignificant; the changes were more obvious in separate periods of an annual cycle of training. The Roufier index in the last year of the Olympic cycle decreased from 4.04±0.54 to 2.02±046 units.